The Effect of Differences Leachate Concentration and Material Properties on Electrical Conductivity of Volcanic Deposits – Case Studies Piyungan Landfill Bantul Yogyakarta - Jaingot A. Parhusip; Agung Harijoko; Doni Prakasa Eka Putra; Wiwit Suryanto (Geological Engineering Department Universitas Gadjah Mada, 2016)
Monitoring at the contaminated subsurface soil, have been conducted by using the geophysical surface method, especially for geoelectrical resistivity method. Monitoring is commonly conducted by using geoelectrical resistivity through measuring the value of Electrical Resistivity (ER) or Electrical Conductivity (EC) of leachate contaminated soil layer. EC measurement value of soil is affected by many factors, among others, particle conduction of soil materials, surface conduction, fluid conduction in the pores as well as the effect of particle shape and soil materials. Piyungan landfill is the main disposal site of Yogyakarta municipal solid waste. This landfill located mainly on the tertiary rocks of volcanic rocks and its weathering products. In order to improve the accuracy of geoelectrical measurements on resistivity in monitoring soil layers from contaminated leachate on this area, this research conducted several measurements on physical properties of soil sample and electrical properties of leachate in the saturated soil samples. The measurement of physical properties includes: porosity, clay content, particle content, and cation exchange capacity (CEC) value. The soil samples were collected from 3 locations around Piyungan Landfill. Type of soils are taken from the alluvial deposits (Sample B), weathered tuffaceous sandstone-claystone (Sample D), and weathered andesitic breccia (Sample F). Samples were made in containers, saturated with aquades-leachate solution with 12 different concentration levels. Electrical conductivity (EC) was measured by using Soil Box Miller and Geoelectric Resistivity Oyo McOhm. According to results of physical properties analysis, the grain size of soils are dominantly sandy clayey silt in grain size distribution, with clay content ranging from 33.0–38.4 %, the CEC values ranging from 26.8–52.7 meq/100 gr, and the porosity of samples B, D and F is 58.85 %, 55.30 %, 59.24 %, respectively. Based on the experiments with 12 different leachate concentrations, there is a linear increase in EC of 0.718mS/cm for every increase in electrical conductivity pore fluid (ECf ) 1 mg/l in samples B, while in samples D and F are 0.492 mS/cm and 0.284 mS/cm respectively. Plotting the data of EC vs ECf for each samples and ER vs ECf , it can be concluded the slope ofDEC/DECf differ for each samples and the electrical conductivity value of different concentration of leachate is very sensitive for alluvial deposits compare to the weathered tuffaceous sandstone-claystone and weathered volcanic breccia deposits.